Extração de óleo de semente de graviola (Annona muricata L.) e mangaba (Hancornia speciosa Gomes) : estudo cinético e avaliação da atividade antioxidante - Santos, Michel Franklin dos (2017)
The objective of this work was to evaluate the antioxidant activity of Graviola and Mangaba seed oils by different extraction techniques, as well as to study the kinetic behavior of the extraction in supercritical conditions and pressurized liquid. The supercritical extraction techniques and pressurized ethanol were performed with the pressure variable in the range of 100-200 bar and temperature of 40-80ºC and the pressurized ethanol flow rate of 0.5-1.0 mL min-1 . The results obtained for oil yield with supercritical fluid extraction were better when CO2 + cosolvent ethanol 10.9% (m m -1 ) and 4.6% (m m -1 ) were used in the 200 bar and 40 ° C condition for the seeds of graviola and mangaba, respectively. In the pressurized ethanol extraction the yield was around 12% (m / m) for graviola seed in the condition of 100 bar, 80 ºC and flow rate 1 mL / min, whereas for the mango seed the yield was 8.3% (m / m) in the 200 bar condition; 80 ° C and flow rate 1 mL / min. Regarding Soxhlet extraction the yields were 36% (m / m) and 23.3% (m / m) for graviola and mangaba seeds, in that order. The technique that presented the best quality of oils for the two seeds was the extraction with pressurized ethanol, having the highest amount of total phenolic compounds obtained in graviola seed oil 4751.1 mg EAG / 100 g obtained in the pressure condition of 100 Pub; temperature at 80 ° C and flow rate 1 mL / min, and for the mangaba seed was 2978.4 mg EAG / 100 g at the pressure condition of 200 bar; the best values were also obtained under the same conditions with IC 50 values of 321.0 μg / mL and 506.3 μg / mL for graviola and mangaba seeds , respectively. The chemical profile of the graviola and mangaba oils presented specific phenolic compounds composition that varied among the different extraction techniques. Vitamin E varied among the different extractions to obtain mango seed oil. Vitamin E has not been identified in graviola seed oils. The alternative extraction methods with pressurized fluids were able to obtain oils of the two seeds with superior quality to the oils obtained by conventional extraction.